2009
DOI: 10.1142/s1088424609000541
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical photodynamic therapy in Spain 1: Chemical and photophysical studies on porphycenes and other photosensitizers

Abstract: Photosensitizers approved for clinical useTo date only five drugs have been approved for PDT: porfimer sodium, 5-aminolevulinic acid (ALA) and its methyl ester, temoporfin, and verteporfin (Chart 1).ABSTRACT: Photodynamic therapy (PDT) is a rapidly expanding alternative to the treatment of solid tumors and other highly-proliferative diseases due to its many attractive features: high selectivity, repeatability, and lack of serious adverse effects. The five drugs approved for use in PDT to date suffer from diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…3 Our group has focused on 2,7,12,17-tetraphenylporphycenes (TPPos) 4 that are endowed with excellent in vitro PDT photosensitizing properties. 5 In order to improve the biological compatibility and selectivity of the parental TPPo, some combinatorial approaches 6 and 9-regioselective insertions of functionalities 7 have been achieved. Our previous works showed that the fluorescence quantum yield and the ability to produce singlet oxygen were substantially decreased in 9-amino-2,7,12,17tetraphenylporphycene (9-ATPPo), but not in 9-acetoxy or 9-nitro derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…3 Our group has focused on 2,7,12,17-tetraphenylporphycenes (TPPos) 4 that are endowed with excellent in vitro PDT photosensitizing properties. 5 In order to improve the biological compatibility and selectivity of the parental TPPo, some combinatorial approaches 6 and 9-regioselective insertions of functionalities 7 have been achieved. Our previous works showed that the fluorescence quantum yield and the ability to produce singlet oxygen were substantially decreased in 9-amino-2,7,12,17tetraphenylporphycene (9-ATPPo), but not in 9-acetoxy or 9-nitro derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…indicativo da alta taxa de decaimento radioativo. Alem disso, são caracterizados por ser muito eficiente nos processos de conversão interna, um processo que ainda não é totalmente compreendido 78 .…”
Section: Porficenosunclassified